مزايا قانون االستثمار81 - بوترعة أيمن ماضي عبد الرحمان (المسيلة, 2023)
تعتبر المزايا والتحفيزات التي منحها المشرع الجزائري والتي تهدف في االستثمار رؤوس االموال من خالل التخفيضات والتكاليف في مرحلة اإلنجاز ومرحلة االستغالل للمشروع االستثماري فهي تعد من قبيل عمليات االستقطاب يحفز من خاللها المستثمرين للولوج الى عالم االستثمار وتوظيف أمواله في الدول التي تمنح تلك المزايا. والتي تتماشى مع التنمية االقتصادية التي تنتهجها الدولة والتي تعود بالفائدة للصالح المضافة فيما يخص السلع والخدمات المستوردة أو المقتنات محليا واإلعفاء من حقوق ة واإلعفاء من الرسم على القيمة العام, وتتمثل هذه المزايا في االعفاءات من الحقوق الجمركي س المال وكذا أ للشركات والزيادات في ر التسجيل المفروضة فيما يخص العقود التأسيسية االعفاء من الضريبة على أرباح الشركات واالعفاء من الرسم على النشاط المهني واإلعفاء بعوض والرسم على االستثمار العقاري. واالعفاء من دفع حق نقل الملكية من الرسم العقاري على الممتلكات العقارية التي تدخل في إطار االستثمار لمدة 31 سنوات The advantages and incentives granted by the Algerian legislature, which are aimed at attracting capital investment through reductions and costs at the completion stage and the exploitation stage of the investment project, are considered as attracting processes through which investors are motivated to enter the investment world and invest their money in the countries that grant these advantages . In line with the economic development pursued by the state and benefiting the public interest, these advantages are exempted from customs rights, exemption from value-added duty in respect of imported goods and services or local acquisitions, exemption from registration rights imposed in respect of constituent contracts of companies and capital increases, as well as exemption from corporate profits tax, exemption from professional activity fee, exemption from real estate fee on real property that is included in the framework of investment for a period of 10 years, exemption from payment of the right of transfer of ownership in compensation and fee on real estate investment.
Keywords: مزايا - قانون االستثمار81